2022
DOI: 10.1371/journal.pone.0271590
|View full text |Cite
|
Sign up to set email alerts
|

Wolves and dogs fail to form reputations of humans after indirect and direct experience in a food-giving situation

Abstract: Reputation is a key component in social interactions of group-living animals and appears to play a role in the establishment of cooperation. Animals can form reputations of individuals by directly interacting with them or by observing them interact with a third party, i.e., eavesdropping. Previous research has focused on whether dogs (Canis lupus familiaris) can eavesdrop on humans because of their ability to cooperate with humans, however the results are mixed and if they can eavesdrop, it is unknown whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Our findings not only provide support that attachment affects dogs' performance in social evaluation studies but also may shed some light on the mixed results that have been observed to date within existing social evaluation research. Researchers have long observed inconsistent patterns in dogs' performance on canine social evaluation tasks, with some studies finding that dogs successfully evaluated prosocial and antisocial actors [15][16][17][18]25] and others finding no evidence for successful evaluation [19][20][21][22][23][24]. Our results provide a hint on why researchers may have observed such varying patterns of performance.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our findings not only provide support that attachment affects dogs' performance in social evaluation studies but also may shed some light on the mixed results that have been observed to date within existing social evaluation research. Researchers have long observed inconsistent patterns in dogs' performance on canine social evaluation tasks, with some studies finding that dogs successfully evaluated prosocial and antisocial actors [15][16][17][18]25] and others finding no evidence for successful evaluation [19][20][21][22][23][24]. Our results provide a hint on why researchers may have observed such varying patterns of performance.…”
Section: Discussionmentioning
confidence: 52%
“…However, such canine social evaluation studies have also yielded mixed results to date: see the review in Silver et al [15]. Some studies have found that dogs prefer prosocial over antisocial humans [15][16][17][18], whereas many other studies have found that dogs show no significant preferences when choosing between prosocial and antisocial individuals [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%